2015
DOI: 10.1007/s12035-015-9299-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PGC-1α Influences Mitochondrial Signal Transduction of Dopaminergic Neurons

Abstract: Parkinson's disease (PD) is a common neurodegenerative disease in the elderly. Mitochondrial dysfunction plays an important role in the pathogenesis of PD. Peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) is a powerful transcription factor, interacting with multiple transcription factors and widely involving in the regulation of mitochondrial biogenesis, oxidative stress, and other processes. The present study investigated the neuroprotective effects and signal transduction mechanisms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 47 publications
4
40
0
Order By: Relevance
“…PGC-1 α activated NRF1 and TFAM, which could regulate the nuclear genes encoding proteins associated with mitochondrial respiratory chain and mtDNA replication [13, 19]. COX-I and COX-IV are important members of the mitochondrial respiratory chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGC-1 α activated NRF1 and TFAM, which could regulate the nuclear genes encoding proteins associated with mitochondrial respiratory chain and mtDNA replication [13, 19]. COX-I and COX-IV are important members of the mitochondrial respiratory chain.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, mitochondrial biogenesis is activated by both physiological and pathological procedures, such as cell division, exercise, calorie restriction, oxidative stress, and inflammation [1618]. Mitochondrial biogenesis is regulated by a complex network of factors, including peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1 α ), nuclear factor-erythroid derived 2-related factor 1 (NRF1), and mitochondrial transcription factor A (TFAM) [19]. These transcription factors and coactivators regulate mitochondrial proteins synthesis and mitochondrial DNA (mtDNA) replication.…”
Section: Introductionmentioning
confidence: 99%
“…Increased PGC-1α expression could improve dopaminergic neuronal viability and mitochondrial activity in in vivo and in vitro PD models (Mudò et al, 2012; Ferretta et al, 2014; Mäkelä et al, 2016). Our previous work has also suggested that the up-regulation of PGC-1α may have a significant impact on mitochondrial signal transduction by up-regulating the expression of ERRα, NRF-1, NRF-2 and PPARγ (Ye et al, 2016). Meanwhile, PD patients exhibit declining levels of cellular bioenergetic-related gene expression that closely corresponded to the level of PGC-1α (Zheng et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…In a comprehensive study [4], the expression of PGC-1α significantly increased after H2O2 challenge in 10T1/2 cells, which effect was recapitulated by others on C2C12 muscle cells [13]. This is in correspondence with our recent findings of significantly increased PGC-1α mRNA expression in the CNS of mice intoxicated with the neurotoxin 3-nitropropionic acid (3-NP), an irreversible inhibitor of complex II [14], and with a similar finding by others on SH-SY5Y cells using 1-methyl-4-phenylpyridinium (MPP+), an irreversible inhibitor of complex I [15]. Furthermore, RNAi against PGC-1α reduced the baseline expression of Mn-SOD (SOD2), Cu/Zn-SOD (SOD1), and GPX in 10T1/2 cells, whereas the expression of Mn-SOD, Cu/Zn-SOD, and peroxisomal CAT was found reduced in the heart and brain of PGC-1α-deficient mice [4].…”
Section: The Role Of Pgc-1α In Concerting Antioxidant Responsessupporting
confidence: 92%
“…Calling for a potential therapeutic relevance in PD, the overexpression of PGC-1α demonstrated neuroprotection against α-synuclein-induced toxicity in vitro [51,56] and in PGC-1α-deficient mice in vivo [17], against MPP+ [15] and rotenone toxicity in vitro [51], and in a parkin interacting substrate (PARIS) overexpression model of PD in vivo [53]. In line with these, transgenic overexpression and resveratrol-induced activation of PGC-1α (via deacetylation by Sirt-1) both rendered neuroprotection against MPTP toxicity in mice [57].…”
Section: Parkinson's Diseasementioning
confidence: 99%